Deferred statistical convergence of order ? in metric spaces - Et, Mikail; Cinar, Muhammed; Kandemir, Hacer Sengul (Amer Inst Mathematical Sciences-Aims, 2020)
In this paper, the concepts of deferred statistical convergence of order alpha and deferred strong Cesaro summability are generalized to general metric spaces and some relations between deferred strong Cesaro summability of order alpha and deferred statistical convergence of order alpha are given in general metric spaces.
Keywords: metric space; statistical convergence; deferred statistical convergence